Culture of animals in antiquity : a sourcebook with commentaries - Llewellyn-Jones, Lloyd (Routledge, 2018)
"The Culture of Animals and Antiquity provides students and researchers with well-chosen and clearly-presented ancient sources in translation, some of which may be well-known, and others undoubtedly unfamiliar, but all central to a key area of study in ancient history -the part played by animals in the cultures of the ancient Mediterranean, practical and cultural. It brings new ideas to bear on the wealth of evidence, literary, historical and archaeological, which we possess for the experiences and roles of animals in the ancient world." --